Constructing Emotional Meaning Through Deixis: A Semantic Analysis of Deictic Expressions in Adele’s "Someone Like You” - Kristin Permata Sari Manalu; Bernieke Anggita Ristia Damanik (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2026)
This research examines how deictic markers in Adele’s well‑known song "Someone Like You" generate emotional significance through a semantic lens. Using a mixed approach that combines qualitative identification and quantitative frequency counts, the study isolates five categories of deixis—person, temporal, spatial, discourse, and social—within the lyric text. The analysis tracks how each type shifts its reference according to the song’s narrative context and maps those shifts onto the emotional states expressed across verses, chorus, bridge, and outro. The findings show that person deixis (I, you, someone) appears most often, building both intimacy and psychological distance. Temporal markers (never mind, sometimes) evoke nostalgia and regret, while spatial terms (here, there) mark emotional separation. Discourse connectors (but, so, and) weave the lyrical fragments into a coherent story, and a clear shift in deictic center moves the listener’s perspective from observer to dialogue participant to solitary reflector. These results confirm that deixis operates as a core semantic device for constructing affective meaning in popular music, directly answering the research questions about how context‑dependent reference produces the song’s emotional arc from longing to acceptance. Practically, songwriters and music educators can apply deictic mapping to enhance emotional storytelling or to teach language‑emotion interplay in lyrics. Future comparative studies across musical genres or languages are suggested to test the generalizability of these patterns.